MOTIVASI IBU RUMAH TANGGA BEKERJA DI PT KIRIN MIWON FOODS - Rinawati Rinawati; Budiyono Budiyono; Sudarmi Sudarmi (JPG (Jurnal Penelitian Geografi), 2013)
This study aimed to assess the motivation of the housewife working in PT Kirin Miwon Foods Sand Mountain Village Sekampung Udik Jaya subdistrict of East Lampung regency. Pressure point studies on maternal education level of household, the income of the family head, the distance to the plant, the outpouring of hours of work, income mothers and housewives revenue contribution to the family income. This study uses descriptive. The study population by 31 housewives all respondents. Data collection by observation, structured interviews, and documentation. Analysis of data with a single table and percentages as the basis of interpretation and description in making this research report. The results showed that: (1) A total of 51.61% of respondents said that low-income heads of households (Rp 901.500/month) causes a housewife working (2) Distance to the house with the plant near an average of 2 km to motivate at-home mom household work (3) the amount of the average wage of Rp 1.709.000/month a housewife motivation to work in a factory (4) Contribution income housewives average height amounted to 61.67% (Rp 1.450.500/month) of the family income (5) Compliance with minimum basic needs are met 100% (31 respondents) after the contribution of the housewife.Keywords: motivation, work, housewife